Taking control with time management - Weeks, M. J. ([American Management Association], 2004)
How to balance the demands of work and personal life. Apply the tools and techniques in this book to meet contemporary time challenges and balance the demands of work and personal life. Now packed with exercises and application tools, this up-to-the-minute revision of the classic gives you proven time management strategies to increase your productivity and your efficiency. You'll discover how to use effective systems for setting and achieving your goals and reducing on-the-job stress. You will learn how to: Conduct a personal time audit Conquer time wasters, including pitfalls of e-mail, cel.
Publisher from copyright statement. - Includes bibliographical references (pages 125-126). - Print version record
Keywords: Time management -- Study and teaching; Gestion du temps; Étude et enseignement; BUSINESS & ECONOMICS; Time Management; SELF-HELP; Time Management; Time management; Study and teaching